Prevalence of non-adherence to physical activity among type 2 diabetes patients. / Sabila Stanirun - Stanirun, Sabila (2016)
Diabetes is the major health problem in the worldwide and there was a high prevalence of diabetes patients in Malaysia. Thus, there is need to encourage people with type 2 diabetes to control their blood glucose with diet and physical activity. Nonadherence to physical activity is the major problem in the management of diabetes type 2. The prevalence of diabetes in Malaysia has increased by 31.0% in just 5 years between 2006. Based from this data, we can indicate that Malaysia is just like other country that is having a problem with increasing the number of patients with diabetes mellitus by year, The increasing number of diseases can give burden to the community and government in aspect of cost in promoting and management of healthy lifestyle modification among them The study will be conducted to identify the prevalence of type 2 diabetes patients that do not adhere with physical activity. Besides, it is to determine the relationship between non-adherences to physical activity among type 2 diabetes patient with socio-demographics data. In this study, we were performing a cross-sectional study in which the data will be collected based on the questionnaire that will be given to the respondents at Klinik Kesihatan Shah Aim. The numbers of respondents were 235 persons. All patients who fulfilled the inclusion and exclusion criteria for this study were the respondent and random sampling method will be applied.The questionnaire has been used as material to collect the dam and information from the respondents. This questionnaire was bilingual, which is in Bahasa Malaysia and English that will be used by the researcher The end of this study the prevalence of type 2 diabetes mellitus patients of Klinik Kesihatan Shah Alam who do not adhere to physical activity were 728%. Then there were association of gender, and working slams with non-adherence to physical activity. This study concludes that high prevalence of path-mm with type 2 diabetes mellitus who were not adhering to physical activity.